2021
DOI: 10.3389/fmed.2021.573726
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Caused by Imported Cases Abroad for the Prevention and Control of COVID-19 in China

Abstract: Background: Overseas imported cases of COVID-19 continue to increase in China, so we conducted this study to review the epidemiological characteristics of these patients.Methods: From February 26 to April 4, 2020, the imported cases from abroad were enrolled in this study. The effect of prevention countermeasures in curbing the spread of COVID-19 was assessed in this study. Moreover, we defined incubation period and confirmed time as from the date of leaving the epicenter to date of symptom onset and date of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…We identified 5012 records through PubMed, EMBASE, and Science Direct database searches, and documented the study selection process in a flowchart and showed the total numbers of retrieved references and the numbers of included and excluded studies (Figure 1). Based on the inclusion and exclusion criteria, 142 articles (8112 patients) were selected for analysis …”
Section: Resultsmentioning
confidence: 99%
“…We identified 5012 records through PubMed, EMBASE, and Science Direct database searches, and documented the study selection process in a flowchart and showed the total numbers of retrieved references and the numbers of included and excluded studies (Figure 1). Based on the inclusion and exclusion criteria, 142 articles (8112 patients) were selected for analysis …”
Section: Resultsmentioning
confidence: 99%
“…China has strengthened control over people living abroad following the COVID-19 outbreak, which also limited the spread of imported diseases such as dengue fever and malaria. At the same time, the country forbids the consumption of live wild animals, and people's awareness of protection is enhanced, which also reduces the possibility of cross-border transmission of infectious diseases to a certain extent (29). The year-on-year increase in the incidence of brucellosis was related to the "Lanzhou Event" in China in 2020, which led to the outbreak of brucellosis, the increase in detection quantity, and the increase in the number of reported cases (30).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, on March 15, 2020, the World Health Organization (WHO) declared the COVID-19 outbreak as a global pandemic ( 3 ). With the reversal of the epidemic at home and abroad, China was faced intense pressure due to imported cases ( 4 ).…”
Section: Introductionmentioning
confidence: 99%